GHANAIAN STUDENT NURSES’ ATTITUDES TOWARDS MATHEMATICS - Florence Christianah Awoniyi; Ugorji Iheanachor Ogbonnaya (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This study aimed to examine the attitudes of Ghanaian student nurses towards mathematics. A sample of 301 undergraduate nursing students at a university in Ghana, selected through census sampling techniques from the first to the third-year students, participated in the study. Data was collected using a 5-point Likert scale questionnaire and analyzed using descriptive and inferential statistics. The study revealed that the students’ attitudes towards mathematics are determined by the value they attach to mathematics and their interest in mathematics. At α=0.01, Spearman's rho correlation coefficient of rs = 0.619 was significant. This indicates that the more value the student nurses attach to mathematics learning, the more interest they will likely have in learning the subject. The coefficient of determination (R2=38%), indicates that the students’ value for mathematics accounts for 38% of the variability in their interest in mathematics.